Economic growth and income inequality in Sudan: an empirical investigation - Atif Awad Abdallah, (Penerbit Universiti Kebangsaan Malaysia, 2010)
This article examined from an empirical point of view the relationship between economic growth and income inequality in Sudan. In particular, the study tested Kuznets’ hypothesis which suggests that the relationship between the two variables took the form of an inverted U-shape curve. The importance of the study stems from the fact that pro-poor economic growth is often seen as important for poverty reduction not only through raising incomes but also in improving the distribution of income in favour of the poor. Ordinary least squares (OLS) technique is applied to crosssection data covering 36 provinces in Sudan for the year 1996. The data on the Gini coefficient and nominal average income are obtained from the 1996 Migration and Labour Force Survey, while the consumer price index for the year 1990 is obtained from the Central Bureau of Statistic. These data are used to estimate the relationship between Gini coefficient and real per capita income. The empirical result suggests that there is a positive relationship between income growth and the inequality parameter, while the Kuznets’ hypothesis is not confirmed by the empirical results. These result indicates that the economy has not yet reached the Kuznets’ turning point beyond which income growth leads to less inequality.